2003
DOI: 10.1002/app.12019
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of carbon black from waste automobile tires

Abstract: Carbon black, an important ingredient in tires, was regenerated from waste automobile tires. Waste tires were cut to separate the tread cap, tread base, side wall, and inner ply and were crushed and pyrolyzed in a muffle furnace at 430°C for 3 h. This black was again heated at 430°C for 1.5 h to increase the surface area to get regenerated black (RB). To find out the effect of heating during pyrolysis, the original black was also heated at 430°C for 1.5 h to get heat-treated black (HTB). The regenerated black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Waste tyres are shredded into fines and are mixed with some reclaiming agents to yield reclaimed tyres. Nonetheless, it is reported that only 5% of the total waste tyres is reclaimed [2,23]. Even though the waste tyres are used for various applications as discussed above, the proportion of waste tyres employed for recycling is insignificant.…”
Section: Moisture and Ash Free Basismentioning
confidence: 99%
See 1 more Smart Citation
“…Waste tyres are shredded into fines and are mixed with some reclaiming agents to yield reclaimed tyres. Nonetheless, it is reported that only 5% of the total waste tyres is reclaimed [2,23]. Even though the waste tyres are used for various applications as discussed above, the proportion of waste tyres employed for recycling is insignificant.…”
Section: Moisture and Ash Free Basismentioning
confidence: 99%
“…The standard analysis pertaining to the determination of properties of carbon black is given in Table 4 [13,23,37,41,66,67]. Carbon black, as such, has the potential to be used as fuel.…”
Section: Carbon Blackmentioning
confidence: 99%
“…Recycling tires can be very difficult due to the thermosetting nature of the crosslink molecular structure. Several methods for recycling tires have been developed such as nitric acid digestion, electric and calorific energy conversion, and pyrolysis in a vacuum or inert atmosphere 1. The main purpose is to recover some carbon compounds and to destroy any hazardous components within the tires.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for recycling tires have been developed such as nitric acid digestion, electric and calorific energy conversion, and pyrolysis in a vacuum or inert atmosphere. 1 The main purpose is to recover some carbon compounds and to destroy any hazardous components within the tires. Tire pyrolysis has proven to be a good method for the recovery of carbon in solids up to 93% by weight at 450 C. 2,3 In previous work, a solid powder that was obtained from car tires by pyrolysis and thermal shock was fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The Evotherm warm-mix CRMA mixture with DAT as warm mix agent (Ev-DAT warm-mix CRMA mixture) is more energy-efficient by saving approximately 108.56 MJ of energy and reducing gas emissions during mixing and paving by at least 32% and 73%, respectively. This model can improves the technical standard of warm-mix CRMA and the energy conservation assessment.Currently, most waste tires are treated as solid waste and are burned or dumped in landfills [4]. In 2007, the quantity of waste tires made into tire-derived fuel in the United States exceeded half of their annual tire yield, while the other 17.2% and 12.2% of waste tires were used as ground rubber materials and civil engineering materials respectively [5].…”
mentioning
confidence: 99%